Factors Influencing Antibiotic Prescribing Behavior and Understanding of Antimicrobial Resistance Among Veterinarians in Assam, India - Eltholth, Mahmoud; Govindaraj, Gurrappanaidu; Das, Banani; Shanabhoga, M. B.; Swamy, H. M.; Thomas, Abin; Cole, Jennifer; Shome, Bibek R.; Holmes, Mark A.; Moran, Dominic (Frontiers in Veterinary Science, 2022)
This study investigates factors influencing veterinarians’ antibiotic prescribing behaviours and their understanding of antimicrobial resistance (AMR). The study used a telephone survey of 50 veterinarians conducted in five districts in Assam state, India. The survey sought information on the most prevalent animal diseases, veterinarians’ awareness of potential preventive measures, including factors determining antimicrobial prescribing; the types of antimicrobials used for different health conditions in different species, and possible options to reduce antimicrobial use (AMU). The majority (86%) of respondents worked for the government, 98% reported have no written policy for the use of veterinary health products, and 58% have no on-site diagnostic facilities. Ceftriaxone, Enrofloxacin, and Oxytetracycline were the antibiotics (ABX) most frequently prescribed, by 76%, 68%, and 54% of veterinarians respectively. These ABX were prescribed mainly for respiratory health problems and mastitis in cattle, and gastrointestinal infections in buffaloes, sheep, goat and pigs. Severity of clinical symptoms, economic status of the livestock owner, and withdrawal period for ABX were ranked as very important factors for giving ABX. Less than two thirds (64%) were aware of the government ban for Colistin and only 2% were aware of a national plan for AMR. This study highlighted that ABX prescription is mostly based on tentative diagnosis given the lack of diagnostic facilities in most veterinary clinics. There is a need to enhance veterinary healthcare and to improve communication between policy makers and field veterinarians and, importantly, a need to disseminate clear prescribing guidelines on prudent AMU.